If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 4x + -6y = 10 Solving 4x + -6y = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 4x + -6y + 6y = 10 + 6y Combine like terms: -6y + 6y = 0 4x + 0 = 10 + 6y 4x = 10 + 6y Divide each side by '4'. x = 2.5 + 1.5y Simplifying x = 2.5 + 1.5y

| 0.5(-4x-5)=7x-0.5 | | 11-2(3m-10)=5(4-m) | | 3-3(x+5)=16 | | 0.75f-0.5=2f+0.5 | | -30=x-10+11x | | -8*-.2= | | 1.5x+6=2x | | x-4=5x+13 | | 12m-9=4m+15 | | 0.5b+0.6=2b-0.9 | | 2.5n-(-8.2)=26.7 | | 3y+3=-18 | | 4(t-5)+2=t+3 | | 0.6p=2c-7 | | 4(2y+9)=3y-14 | | -0.7y-56=-3.5 | | 7-6a=6-7a | | x(4.8-2)=4.8x-2 | | 6x+6=-48 | | 5-9.2d=32 | | 2(r-4)=5(r+-7) | | 9x+x=25 | | -4y+12=-28 | | 2(3h-1)+4h=10(2-3h)+38h | | 3(5m-1)-7m= | | 2(3h-1)4h=10(2-3h)+38h | | 50=-2+13q | | 0.3(p+4)=2.7p | | 3-(2-f)+1=2(2-f) | | 7+23x=35+16x | | 3(d+1)=3+4(d+5) | | 7=-3.4x | | 5(b-6)=3+8(b+9) | | 10x=25 | | 9(z+1)=-3(5+z) | | 6(-3x+8)=-5(3x-7) | | -5.8+m=1.3 | | -4(1+x)=5(1-x) | | s=(n-2)180 | | 8x-4-3x=21 | | 2(v+1)=6v-64 | | 10k+3=6k-15 | | 7t+4=2(7t-5) | | 3(3.4)= | | 3r=2(7+5r) | | 8(3.4)= | | 4x+11X=105 | | 7y-4(3y-5)=80 | | -2(2p-3)=2p | | 26=-5(4+8y)-6 | | 3(2x+5)=24 | | 4x= | | 20-3(m-1)=-4 | | 2a-11=-8a+19 | | 7(2-j)-5=30 | | 7(x+2)-4= | | 3(5i-2)+2=26 | | -5.5+2.3= | | 7x+2-4= | | -4-6(2-k)=8 | | -9+2(x+6)=28 | | 5(n+2)=3n | | 2.3-5(1.1)=7.8 | | 8(7-3q)=-17q | | 3(2-x)=2(x+8) |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics